2002
DOI: 10.1016/s0002-9440(10)64160-0
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection of Cathepsin D Induces Caspase-Dependent Apoptosis in Fibroblasts

Abstract: Apoptosis, or programmed cell death, occurs through activation of a cell suicide process that is regulated by many different intracellular and extracellular events. During apoptosis, the cell is degraded through activation of proteases and endonucleases. The class of proteases known as caspases plays an essential role in the induction and execution of apoptosis, and, when activated, they acquire the ability to cleave key intracellular substrates that results in the biochemical and morphological changes associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
124
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(132 citation statements)
references
References 25 publications
6
124
0
2
Order By: Relevance
“…Genetic evidence for the role of cysteine cathepsins in apoptosis is provided by studies showing resistance against TNF-induced liver apoptosis in mice lacking cathepsin B ( 19 ), perhaps because of insuffi cient cleavage of Bid ( 21 -23 ). Cathepsin D was shown to activate Bax in T cells ( 24 ) and to be involved in the release of cytochrome c from mitochondria in fi broblasts ( 20,25 ). Moreover, pepstatin A (PepA), a pharmacological inhibitor of cathepsin D, blocked mitochondrial cytochrome c release and caspase activation in cardiomyocytes and fi broblasts ( 25,26 ).…”
Section: Cathepsin D Translocation Precedes Cytochrome C Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic evidence for the role of cysteine cathepsins in apoptosis is provided by studies showing resistance against TNF-induced liver apoptosis in mice lacking cathepsin B ( 19 ), perhaps because of insuffi cient cleavage of Bid ( 21 -23 ). Cathepsin D was shown to activate Bax in T cells ( 24 ) and to be involved in the release of cytochrome c from mitochondria in fi broblasts ( 20,25 ). Moreover, pepstatin A (PepA), a pharmacological inhibitor of cathepsin D, blocked mitochondrial cytochrome c release and caspase activation in cardiomyocytes and fi broblasts ( 25,26 ).…”
Section: Cathepsin D Translocation Precedes Cytochrome C Releasementioning
confidence: 99%
“…1, A and B ). To investigate the eff ect of pharmacological inhibition of cathepsin B and D, we used the previously characterized specifi c cathepsin inhibitors CA-074-ME (CA), a cell-permeable inhibitor of cathepsin B and possibly other cysteine cathepsins ( 29 ), and PepA, which, as mentioned in the Introduction, blocks the aspartic protease cathepsin D ( 20 ).…”
mentioning
confidence: 99%
“…14,15 Lysosomes may trigger different forms of cell death depending on the cell types and the stimuli. 16,17 Pathways of lysosomal origin may lead to apoptosis associated with caspases while the release of lysosomal proteases, such as the cysteine cathepsins B and L and the aspartyl cathepsin D, may cause necrosis, apoptosisor necrosis-like cell death. 18,19 Calpains, cytosolic calcium-activated neutral cysteine proteases, are, at least in part, also associated with lysosomes.…”
Section: Introductionmentioning
confidence: 99%
“…19 Similarly, PC12 cells overexpressing cathepsin D died more rapidly than wild-type cells in serum-deprived culture, 20 and microinjection of cathepsin D into the cytosol of human fibroblasts caused apoptosis. 21 Further support that cathepsin D might be involved in cell death signaling came from studies in which pepstatin A, an aspartic protease inhibitor, was reported to block cell death induced by interferon-gamma, Fas/APO-1, 19 tumor necrosis factor-a (TNF-a), 22 camptothecin, 23 naphthazarin, 24,25 the synthetic retinoid CD437 26 or hydrogen peroxide. 27 However, this concept has been challenged by very recent reports that have demonstrated that cathepsin D is not directly implicated in the cell death machinery.…”
Section: Introductionmentioning
confidence: 99%